In vitro methods of CLSI to detect Carbapenemases in Carbapenem-resistant Enterobacteriaceae - Sinha, Deepa; G B., Shantala; R., Ambica; C.R., Kusuma (Tropical Journal of Pathology and Microbiology, 2020)
Aims: Detection of Carbapenemases production in Carbapenem Resistant Enterobacteriaceae(CRE) using CarbaNP and its comparison with the newer CLSI recommended modified Carbapenemases Inactivation Method(mCIM). Materials and Methods: 100 isolates of CRE were selected in a period of 3 months from June-August 2018 for the tests, based on MIC values of >= 2mg/ml given by vitek2compact systems. CarbaNP test was performed as per M100, CLSI 2018 guidelines. CarbaNP solutions A and B were prepared and Imipenem-Cilastatin powder was replaced for standard imipenem powder. The reading was taken at the end of 10 mins,30 mins, and 2 hours. mCIM was performed as per CLSI M100,2018. The presence of carbapenemase was indicated by an inhibition zone ≤15mm in diameter. eCIM was also performed in the same way, with 0.1M EDTA added in TSB broth. Descriptive analysis. Results: Among the 100 CRE isolates, Carba NP detected 71 CP-CRE while mCIM detected 80(80%) of the same. mCIM detected 8 more positives than the carbaNP test. 1 isolate tested positive CarbaNP but tested negative in mCIM. Conclusion: CarbaNP is a novel protocol recommended by CLSI for detecting CP-CREs and studies prove that it is a very good test in detecting KPC and OXA mediated resistance, while mCIM is said to detect all 5 genes i.e. KPC,NDM,OXA,IMP, and VIM. Carba NP is easy to perform and gives quick results once the reagents are prepared. mCIM on the contrary as a newly developed test detects more CP-CREs but takes more time for the interpretation. However, further confirmation of carbapenemases enzymes with molecular methods in the present study was not done.